Biological bases of cancer: a proposal of minimum contents for health schools (International Journal of Medical and Surgical Sciences, 2021)
Cancer constitutes the second most common cause of death worldwide and is expected to become the leading one, even above cardiovascular diseases. The understanding of the cellular and molecular basis of cancer has led not only to the proper development of chemotherapy but also of target therapies. Although these advances are related with improved survival rates among cancer patients, it has poorly impacted its incidences. In this regard, the lack of knowledge regarding the impact that the several carcinogenic factors and their interactions have on different types of cancers may explain at least in part the difficulties to reduce incidence rates. However, is worth noticing that in several health schools of Chilean universities, cancer does not constitute a formal course, being only partially approached during other courses, such as cell biology, internal medicine, and surgery. Thus, the aim of our work is to provide students a simple and resumed manuscript about essential topics necessary to understand the biological basis of cancer. First, the reader will find some fundamentals about human biology including the cell cycle and the central dogma of molecular biology, which offers an overview of the physiological mechanisms leading to malignant neoplasia. Then, we will provide current definitions of neoplasia, benign and malignant tumors are provided. Finally, the different stages of tumor progression will be approached to allow the understanding of cancer development. These stages include (i) initiation, (ii) promotion, and (iii) progression. For the last one, metastasis, angiogenesis, extracellular matrix degradation, migration, and immune evasion will also be addressed. This work will not consider the metabolic hypothesis of cancer.
Keywords: cancer; neoplasia; mutation; polymorphisms; proto-oncogenes; metastasis